2015
DOI: 10.25011/cim.v38i4.24262
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of Diffusion-Weighted Magnetic Resonance Imaging in Diagnosis of Bladder Cancers

Abstract: Purpose: Our study is designed to examine the diagnostic performance of diffusion-weighted magnetic resonance imaging (DW-MRI) for bladder cancers (BC), and to determine whether DW-MRI can differentiate muscle invasive bladder cancer (MIBC) from non-MIBC (NMIBC).Methods: A meta-analysis was performed of published studies that investigated the performance of DW-MRI for BC. These studies were retrieved from scientific literature databases using sensitive electronic search strategies. The STATA 12.0 and Meta-disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 32 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Several studies (6,10,11,(17)(18)(19)21) have had a wide range of partially conflicting results for DWI MR imaging in differentiating T1 or lower tumors from T2 or higher tumors. This motivated researchers to perform a recently published meta-analysis (33), which included eight studies published before September 2014 in English or Chinese. It involved 259 T2 or higher lesions and 515 T1 or lower lesions.…”
Section: Evidence-based Practice: Diagnostic Value Of Mr Imaging In Dmentioning
confidence: 99%
“…Several studies (6,10,11,(17)(18)(19)21) have had a wide range of partially conflicting results for DWI MR imaging in differentiating T1 or lower tumors from T2 or higher tumors. This motivated researchers to perform a recently published meta-analysis (33), which included eight studies published before September 2014 in English or Chinese. It involved 259 T2 or higher lesions and 515 T1 or lower lesions.…”
Section: Evidence-based Practice: Diagnostic Value Of Mr Imaging In Dmentioning
confidence: 99%
“…These evaluations of MRI are limited by small sample sizes and variable techniques. Previous meta‐analyses on MRI for staging of bladder cancer are limited by restricted focus on the index test (e.g., DWI only ) or focus on only one threshold of disease (e.g., ≤T1 vs ≥T2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al[54] meta-analysis reported the differences in ADC values between benign renal lesions (2.47 ± 0.81 × 10 -3 mm 2 /s) and malignant renal lesions (1.81 ± 0.41 × 10 -3 mm 2 /s) with a P value < 0.001. DWI is also studied in bladder malignancies, especially to evaluate the depth of invasion, deciding the T stage of bladder cancer which decides the management protocol[57,58]. Management of urinary bladder cancer is primarily determined on distinguishing superficial tumors (stage T1 or lower) from invasive ones (stage T2 or higher).…”
Section: Applications Of Dwi In Oncologymentioning
confidence: 99%